Supplemental oxygen therapy does not affect the systemic inflammatory response to acute myocardial infarction. (11th December 2017) - Hofmann, R.; Tornvall, P.; Witt, N.; Alfredsson, J.; Svensson, L.; Jonasson, L.; Nilsson, L.
Abstract: Background: Oxygen therapy has been used routinely in normoxemic patients with suspected acute myocardial infarction (AMI) despite limited evidence supporting a beneficial effect. AMI is associated with a systemic inflammation. Here, we hypothesized that the inflammatory response to AMI is potentiated by oxygen therapy. Methods: The DETermination of the role of Oxygen in suspected Acute Myocardial Infarction (DETO2X‐AMI) multicentre trial randomized patients with suspected AMI to receive oxygen at 6 L min −1 for 6–12 h or ambient air. For this prespecified subgroup analysis, we recruited patients with confirmed AMI from two sites for evaluation of inflammatory biomarkers at randomization and 5–7 h later. Ninety‐two inflammatory biomarkers were analysed using proximity extension assay technology, to evaluate the effect of oxygen on the systemic inflammatory response to AMI. Results: Plasma from 144 AMI patients was analysed whereof 76 (53%) were randomized to oxygen and 68 (47%) to air. Eight biomarkers showed a significant increase, whereas 13 were decreased 5–7 h after randomization. The inflammatory response did not differ between the two treatment groups neither did plasma troponin T levels. After adjustment for increase in troponin T over time, age and sex, the release of inflammation‐related biomarkers was still similar in the groups. Conclusions: In a randomized controlled setting of normoxemic patients with AMI, the use of supplemental oxygen did not have any significant impact on the early release of systemic inflammatory markers.